United nations resolutions on Palestine and the Arab-Israeli conflict - UNITED... (Institute for Palestine Studies, 1975)
Oen, Jil.1=c.1-2; Jil. 2=c.1-2;Jil.3=c.1-3;Jil.4=c.1-2/ tr, jil.1=c.3; jil.2=c.3; jil.4=c.3